Dystrophin Is Required for the Proper Timing in Retinal Histogenesis: A Thorough Investigation on the mdx Mouse Model of Duchenne Muscular Dystrophy - Persiconi, Irene; Cosmi, Francesca; Guadagno, Noemi Antonella; Lupo, Giuseppe; De Stefano, Maria Egle (Frontiers in Neuroscience, 2020)
Duchenne muscular dystrophy (DMD) is a lethal X-linked muscular disease caused by defective expression of the cytoskeletal protein dystrophin (Dp427). Selected autonomic and central neurons, including retinal neurons, express Dp427 and/or dystrophin shorter isoforms. Because of this, DMD patients may also experience different forms of cognitive impairment, neurological and autonomic disorders and specific visual defects. DMD-related damages to the nervous system are established during development, suggesting a role for all dystrophin isoforms in neural circuit development and differentiation; however, to date, their function in retinogenesis has never been investigated. In this large-scale study, we analyzed whether the lack of Dp427 affects late retinogenesis in the mdx mouse, the most well studied animal model of DMD. Retinal gene expression and layer maturation, as well as neural cell proliferation, apoptosis and differentiation, were evaluated in E18 and/or P0, P5, P10 and adult mice. In mdx mice, expression of Capn3, Id3 (E18-P5) and Dtnb (P5) genes, encoding proteins involved in different aspects of retina development and synaptogenesis (e.g., Calpain 3, DNA-binding protein inhibitor-3 and -dystrobrevin, respectively) was transiently reduced compared to age-matched wild type mice. Concomitantly, a difference in the time required for the retinal ganglion cell layer to reach appropriate thickness was observed (P0-P5). Immunolabeling for specific cell markers also evidenced a significant dysregulation in the number of GABAergic amacrine cells (P5-P10), a transient decrease in the area immunopositive for the Vesicular Glutamate Transporter 1 (VGluT1) during ribbon synapse maturation (P10) and a reduction in the number of calretinin+ retinal ganglion cells (RGCs) (adults). Finally, the number of proliferating retinal progenitor cells (P5-P10) and apoptotic cells (P10) was reduced. These results support the hypothesis of a role for Dp427 during late retinogenesis different from those proposed in consolidated neural circuits. In particular, Dp427 may be involved in shaping specific steps of retina differentiation. Notably, although most of the above described quantitative alterations recover over time, the number of calretinin+ RGCs is reduced only in the mature retina. This suggests that alterations subtler than the timing of retinal maturation may occur, a hypothesis that demands further in-depth functional studies.